2018
DOI: 10.5851/kosfa.2018.e26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ground Chopi (Zanthoxylum piperitum) on Physicochemical Traits and Microbial Community of Chicken Summer Sausage during Manufacture

Abstract: Changes in microbial community and physicochemical traits of chicken summer sausage made from spent layer thigh added with different level (0%, 0.1%, 0.3%, and 0.5% w/w) of ground chopi (Zanthoxylum piperitum) during manufacture were analyzed. The microbial community was profiled and analyzed by sequencing 16S rRNA gene using Illumina MiSeq. Samples were taken from raw sausage batter, after 15 h of fermentation, 8 h of cooking including cooling down, and 7 d of drying. The final pH of the sausage was reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These results suggest that the microbial diversity of skate fermentation is determined at around day 10. Several studies have shown that the diversity of bacteria in fermented food or meat decreases at a specific time or stage according to acidic or alkaline conditions [ 15 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that the microbial diversity of skate fermentation is determined at around day 10. Several studies have shown that the diversity of bacteria in fermented food or meat decreases at a specific time or stage according to acidic or alkaline conditions [ 15 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…are the predominant microorganisms after fermentation. These bacterial groups produce lactic acid, which prevents the growth of pathogenic bacteria and improves the flavor [ 15 , 32 , 33 ]. In alkaline fermented protein foods such as traditional eggs (Pidan) and soybean pastes (Doenjang, Gochujang, and Natto), Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PO and LO are rich in proteins, the effects of acidic or alkaline conditions on proteins affect the properties of PON and LON. 18,41 Strong alkaline condition also affected the chemical properties of PO and LO protein, which led to the proteinparticle binding. Although the particle size of the emulsion changes within this pH range, the change in particle size was very small (<5 nm) with little effect.…”
Section: The Inuence Of Ph On Pon and Lonmentioning
confidence: 99%
“…Utama D. T. et al reported the use of PO and canola oil as raw materials to replace the animal fat method, which opened up a new direction for the application of nanoemulsion. 18 Huang J. et al studied the preparation of primary emulsions using Tween20 and lecithin as emulsifiers and prepared a lecithin–chitosan film multilayer emulsion of the LO by layer-by-layer electrostatic deposition. 19 In many studies on nanoemulsion, they contain a single nonionic surfactant; however, the mixed surfactants have better properties than single surfactants.…”
Section: Introductionmentioning
confidence: 99%